Evaluation of Singapore as an association hub. - Ho, Aileen Yee Pei. (2008)
This study was done in collaboration with Singapore Tourism Board (STB) to update the Tourism 21 Master Plan. It identified factors that attract associations to relocate their headquarters to Singapore and also profiled the type of associations that would be attracted to Singapore.